PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ADOBE FLASH CS6 UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PADA MATERI KESETIMBANGAN KIMIA - Lenni Khotimah Harahap; Anggi Desviana Siregar (JPPS (Jurnal Penelitian Pendidikan Sains), 2020)
This study aims to determine: (1) the feasibility of interactive learning media based on Adobe Flash CS6; (2) differences in motivation and learning outcomes using interactive learning media based on Adobe Flash CS6 and using chemistry learning media on the internet; (3) the influence of motivation on learning outcomes. This study uses R&D ADDIE (Analysis, Design, Development, Implementation, and Evaluation) method. The population was all students of second grade at SMA Negeri 1 Padangsidimpuan. The samples were taken by using purposive sampling, there were 60 students from two classes at the second grade. The data collection instruments were tests and questionnaires. The results: (1) the feasibility of interactive learning media based on Adobe Flash CS6 shows the mean is 4.5, which is very suitable to use; (2) motivation and learning outcomes using interactive learning media based on Adobe Flash CS6 shows 94.7% and 87.17 which is higher than the motivation and learning outcomes using chemistry learning media on the internet, namely 88.5% and 79.67; (3) the effect of learning motivation in learning outcomes using interactive learning media based on Adobe Flash CS6 is 18.6%. The results of this study is used as an input for teachers and prospective teachers in using interactive learning media to create fun learning and increase motivation that will have an impact on learning outcomes.